Targeted Muscle Reinnervation—an Up-to-Date Review: Evidence, Indications, and Technique - Chappell, Ava G.; Ramsey, Matthew D.; Park, Seong; Dumanian, Gregory A.; Ko, Jason H. (Archives of Plastic Surgery, 2025)
Targeted muscle reinnervation (TMR) is a surgical technique originally created to improve prosthetic function following upper extremity amputation. TMR has since been shown to be effective in the prevention and treatment of chronic postamputation phantom and residual limb pain in both upper and lower extremity amputees and for neurogenic pain in the nonamputee patient population. This article provides a current review of the various indications for TMR and surgical techniques, organized by amputation site, timing, and regional anatomy.
Keywords: targeted muscle reinnervation; nerve transfers; painful neuromas; myoelectric prosthesis